Gender difference in drinking among the urban squatters of Nepal - Thapa, Pushpa; Mishra, Shiva Raj (Health Prospect, 2016)
Background: Globally, more men drink than women. However, we remain unknown about this phenomenon among the urban poor of Nepal. The current study investigated gender differences in drinking among the urban poor residing in urban squatter settlements of Nepal. Methodology: We approached 422 households of four squatter settlements of Kathmandu Valley, using modified Gender, Alcohol, and Culture: an International Study questionnaire. Following cross-sectional design, we executed study from November, 2013 to March, 2014. Bivariate and multivariable logistic regression was done in R version 3.1.2. Results: Odds of being current drinker (adjusted odds ratio: 5.86, 95% CI: 2.50-13.72) was higher in men than the women. Men were also more likely to be frequent drinkers (adjusted odds ratio: 6.61, 95% CI: 1.45- 30.11) than their women counterparts. Men and women did not differ significantly in contexts of drinking and types of drinking. Men also carried higher possibility of being current drinker in various strata of socio-demographic characteristics. The respective crude odds ratio were accordingly: (18-24 years: 12.73, 95% CI: 4.13-40.98); (25-44 years: 9.94, 95% CI: 4.54-22.13); (45-65 years: 8.23, 95% CI: 3.70-18.57); (dalit and disadvantaged janajati:9.80, 95% CI: 5.61-17.21); ( upper caste: 9.00, 95% CI: 3.25-25.78); ( Hindu: 8.67, 95% CI: 4.79-15.80); (non-Hindu: 13.64, 95% CI: 5.46-34.88); (secondary and below education: 10.22, 95% CI: 6.01-17.46); (above secondary education:7.00, 95% CI: 2.05-25.06); (employed: 3.94, 95% CI: 1.74-8.99);(unemployed: 14.08, 95% CI: 7.45-26.84); (married: 9.79, 95% CI: 95% CI: 5.27-18.33); (unmarried and others: 9.33, 95% CI: 4.18-21.15). Conclusion: The study revealed significant gender differences in drinking. Gender sensitive and specific alcohol interventions should be planned and implemented covering urban squatter settlements.